Contesting history and identity formation in Paul and in South Africa - Dube, Zorodzai (Hervormde teologiese studies, 2015)
This study compares dynamics in the contestation of history and identity between Paul to post-1994 white Afrikaners in South Africa. In reference to Paul, I am interested in how the followers of the nascent Hellenistic Gentile Christian movement claimed legitimacy as the true Jews, usurping the monopoly of the identity ‘true Jews’ from the Jews, who believed that they alone, stand to claim the Abrahamic promise. Instead, Paul contested the Jewish history and identity, claiming that his Gentile Christians were, in fact, the true Jews – how so? The analysis shall be juxtaposed, providing a discursive analysis to the Afrikaners, who regularly receive claims that they do not belong to South Africa. Specifically, I look into how they contest the South African oral history, claiming that in fact, they are legitimate and the original inhabitants. The study notes that in both cases, identity is constructed through the contestation of history and identity. Thus, the comparison shall be narrowed down to how history is variably, contested for identity formation. Though living within the same locale, the different social groups interpret history differently and variously, appeal to different conspicuous figures and events as their identity markers.